2007
DOI: 10.1007/s11243-007-0213-7
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of iron(III) salen and saloph Schiff bases with bridging 2,4,6-tris(2,5-dicarboxyphenylimino-4-formylphenoxy)-1,3,5-triazine and 2,4,6-tris(4-carboxyphenylimino-4′-formylphenoxy)-1,3,5-triazine

Abstract: Complexes of iron(III) salen and saloph Schiff bases with bridging 2,4,6-tris(2,5-dicarboxyphenylimino-4-formylphenoxy)-1,3,5-triazine and 2,4,6-tris(4-carboxyphenylimino-4¢-formylphenoxy)-1,3,5-triazine Abstract Four new trinuclear Fe(III) complexes involving tetradenta Schiff bases N,N 1 -bis(salicylidene) ethylenediamine-(salenH 2 ) or bis(salicylidene)-o-phenylenediamine-(salophH 2 ) with 2,4,6-tris(2,5-dicarboxyphenylimino-4-formylphenoxy)-1,3,5-triazine (DCPI-TRIPOD) or 2,4,6-tris(4-carboxyphenylimino-4¢… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 20 publications
1
11
0
1
Order By: Relevance
“…Obtained tripodal oxySchiff bases were characterized by their elemental analyses, thermal analyses, 1 H NMR, and FT-IR, AAS and mass spectral data. [34][35][36][37][38][39]. These complexes are the examples of tripodal multinuclear complexes bridged by carboxylate anions to the iron and chromium centers (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Obtained tripodal oxySchiff bases were characterized by their elemental analyses, thermal analyses, 1 H NMR, and FT-IR, AAS and mass spectral data. [34][35][36][37][38][39]. These complexes are the examples of tripodal multinuclear complexes bridged by carboxylate anions to the iron and chromium centers (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…The vibrations of the azomethine C N, triazine C N and C-O-C of the free ligands were observed at 1618-1605, 1574-1560 and 1375-1359 cm −1 range, respectively [34][35][36][37][38]42,43]. In the complexes, the fact that these bands were shifted to lower frequencies has indicated that oxygen atoms of the dendrimeric oxy-Schiff base ligands are coordinated with the ligand complexes.…”
Section: Ft-ir Spectra Interpretations Of the Ligands And Complexesmentioning
confidence: 99%
See 3 more Smart Citations